2017
DOI: 10.1103/physreve.95.012212
|View full text |Cite
|
Sign up to set email alerts
|

Phase reduction theory for hybrid nonlinear oscillators

Abstract: Hybrid dynamical systems characterized by discrete switching of smooth dynamics have been used to model various rhythmic phenomena. However, the phase reduction theory, a fundamental framework for analyzing the synchronization of limit-cycle oscillations in rhythmic systems, has mostly been restricted to smooth dynamical systems. Here we develop a general phase reduction theory for weakly perturbed limit cycles in hybrid dynamical systems that facilitates analysis, control, and optimization of nonlinear oscill… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 75 publications
3
45
0
Order By: Relevance
“…In Refs. [47,48], phase equations for hybrid limit-cycle oscillators have been derived. A generalized adjoint equation with discontinuous jumps is derived and the sensitivity function for the phase is obtained.…”
Section: Generalization Of Phase Reduction To Non-conventional Sysmentioning
confidence: 99%
“…In Refs. [47,48], phase equations for hybrid limit-cycle oscillators have been derived. A generalized adjoint equation with discontinuous jumps is derived and the sensitivity function for the phase is obtained.…”
Section: Generalization Of Phase Reduction To Non-conventional Sysmentioning
confidence: 99%
“…This problem was handled in 2017 by Shirasaka et al, who rigorously defined isochrons for general hybrid systems, and introduced the phase reduction method for weakly perturbed hybrid systems using the saltation matrix [34].…”
Section: Adjoint Methods (Nonsmooth Systems)mentioning
confidence: 99%
“…We adopted this approach with the assumption that there are underlying dynamical systems or limit cycles behind the segmental angles during locomotion. In limit cycles, phase description has been developed for locomotion such as using local joint angles [47,48,49,13] or right heel-contact cycle as global description [50]. Compared with these studies, we extracted global phases at the gait frequency and at additional harmonic frequencies in a data-driven manner.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we confirmed that the theoretical requirements are satisfied for locomotion data from the viewpoint of the convergence of estimation error. Although other locomotion studies obtained phase descriptions using local joint angles [47,48,49,13] or a global one [50], in this study, we obtain global phase descriptions with various frequencies from locomotion data at various speeds. Furthermore, we examine the difference and similarity between the conventional and our approaches by investigating the extracted dynamical information on the conventional coordinative structures.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation